(untitled) (Research, Society and Development, 2021)
Objective: to list evidence through a literature review to better understand Boderline personality disorder, its characteristics, symptoms and the most different treatment approaches as well as the prognosis of these patients. Methodology: This is a bibliographic research developed using the Integrative Review method. The search sources were the database of the Virtual Health Library (VHL) through Latin American and Caribbean Literature in Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE). In addition to these bases, the Scientifc Eletronic Library Online (SciELO) was also used. Results: One hundred and seventy-five (75) occurrences (studies and / or articles) were observed during the primary search, after crossing the descriptors: Personality disorder, Borderline, Treatment. The listed literature brings Borderline as a complex personality disorder that is difficult to diagnose and treat, but there are effective strategies such as the use of psychotropic drugs, cognitive behavioral therapy (CBT), group therapy and in some cases hospitalization. Conclusion: It is possible to conclude about the need to prepare health professionals to support these patients who, several times for not knowing about the disorder, end up not offering an adequate treatment, thus hindering the patient’s evolution. The borderline personality disorder is complex in all its conjuncture from the symptomatology until its diagnosis, being mistakenly confused with other pathologies.